DETEKSI DAN DIFERENSIASI CAMPURAN DAGING BABI DAN SAPI DALAM PRODUK OLAHAN DAGING DENGAN METODE HIGH RESOLUTION MELT ANALYSIS (HRMA) - , WINAHYU ESTRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
An increasingly widespread act of mixing beef meat with pork has caused several food assessment institutions such as Lembaga Pengkajian Pangan Obatobatan dan Kosmetika Majelis Ulama Indonesia (LPPOM MUI) intensified their effort in eradicating processed foods that are contaminated by pork meat. Several detection methods such as Enzym Linked Immunosorbent Assay (ELISA), Fourier Transform Infrared Spectofotometry (FTIR), Polymerase Chain Reaction (PCR), dan Real- Time Polymerase Chain Reaction (Real-Time PCR) are deemed to be flawed and somewhat lacking. High Resolution Melt Analysis (HRMA) is a method that could be applied to analyse DNA with real-time PCR that the melting curves will be immediately formed based on fluorescence produced by the dyes when there is a double-stranded DNA. Fluoresence dyes in that process is evagreen. This research uses pure beef and pork meat as well as meatball samples to acquire pure DNA results. The sample DNA is then amplified with HRMA method using real-Time PCR. The melting curve were identified based on the melting temperature (Tm) of each PCR product/amplicon. The melting curve were analysed using Bio-Rad CFX Manager 3.0. The result of the research has shown significant differences between the samples (beef, pork, and meatball) on the melting curve that was formed. Pork has a higher melting temperature then beef, and meatball sample has melting temperature in between pork and beef. It was shown that the meatballs sample containing pork and beef in it. Based on that result, HRMA is proven as a method that can be used to identify an adulteration in meat and differentiate the types of meat.